MEDICINAL PLANT - MOUNTAIN BASIN (ORIGANUM VULGARE) - Gulshod Usmonova; Gulruxsor Ochilova (International Scientific and Current Research Conferences, 2021)
The article introduces the structure, distribution and composition of the medicinal plant Mountain Basil, its beneficial properties for human health and its use in folk medicine.